Abbreviation usage practices in Cebu Velez General Hospital and Vicente Sotto Memorial Medical Center and perceived effects on medical student training - Tapia, Narciso A.
There have been reports on some abbreviations being misinterpreted causing medication errors. Locally, awareness regarding potentially-dangerous abbreviations is lacking. Abbreviations are not formally taught and there are no related written policies or guidelines. The objectives of this study are to: (1) describe abbreviation usage practices in the Doctors? Orders and History sheet in Cebu Velez General Hospital and Vicente Sotto Memorial Medical Center; (2) determine why medical students and physicians use abbreviations and (3) determine the perceived effects on training of medical students or residents. This is a descriptive cross-sectional study utilizing chart or record reviews, group and key informant interviews. Stratified Random Sampling with Proportionate Allocation was used to select a total of 200 chart records (100 each from CVGH and VCMMC) while purposive sampling was used for key informants. Statistical analysis with level of significance set at 0.05 was made through Chi-square, t-test and Analysis of Variance, using Microsoft Excel 2007 with Analysis ToolPak. Content analysis was done for the interviews. Results showed abbreviations are prevalent in all the departments of both hospitals. Practically all orders contained abbreviations. First initialization is the most common form recorded for the history and orders. However, in the History sheets, there was a significant difference in the proportion of truncating the end forms (p=0.0005), Latin-derived abbreviations (p=0.0025) as well as syllabic abbreviations (p=0.0016) between CVGH and VSMMC as determined by chi-square test. While in the Doctors? Orders, a significant difference in the proportion between the 2 hospitals was observed in the following forms: dose expression and measurement unit (p=0.023), Latin-derived abbreviations (p=0.036) and first letter initialization (0.032). Few abbreviations recorded from the charts in both hospitals belonged to the text language form. Comparing both hospitals, there is no significant difference as to the mean variety of abbreviations. The most common examples are likewise practically similar. Dubious abbreviations and abbreviations in Institute of Safe Medical Practices' Do Not use List were also observed in the doctor's Orders of both hospitals. Key informant and group interviews were also done. These revealed that abbreviations are used as time saver, space saver, confidentially measure; for note-taking to catch up with lectures and for order-writing to catch up with verbal instructions. It is also used for convenience. Poor handwriting is a concern. What can be concluded from the study is that understanding the most common abbreviations from a different department within or outside Cebu Velez General Hospital is likely not a major problem although potential dangers do exist due to some few differences in preference of potentially dangerous abbreviations. Abbreviations affect learning directly and indirectly. Perceived benefits outweigh the potential dangers of abbreviation usage. Overall effect is recognized to be improved patient care and welfare.